The role of mouthwash uses and routine dental visits in dental hygiene among public secondary school students - Stella, Nwankwo Nonyelum (Kuras Institute, 2025)
Purpose− This study utilized a descriptive survey design to assess dental hygiene practices among public secondary school students in Awka Education Zone, Anambra State. Method− Targeting SS2 students in 20 schools, purposive sampling was employed, resulting in a sample size of 1,063 students. Data was gathered using a validated, self-structured questionnaire divided into demographic and research sections, with responses rated on a four-point scale. Reliability testing yielded a Pearson correlation of 0.75. Responses were collected directly in classrooms, and 1,000 completed questionnaires were retrieved. Analysis involved weighted mean scores and standard deviation, with an acceptance threshold of 2.5. Findings− The study found that mouthwash is considered an effective dental hygiene practice among public secondary school students, with mean scores ranging from (2.71) to (2.79). Routine dental visits were also acknowledged for detecting oral issues, with mean scores between (2.63) and (2.81), highlighting the importance of both practices in promoting oral health. Similarly, routine dental visits were recognized for detecting oral issues and maintaining dental health, with average means above the acceptance level, underscoring the importance of dental hygiene practices among students.